Exploring the phenomenon of host confirmity pressure : immigrants' experiences of host conformity pressure in Finland in relation to their acculturation processes - Sommier, Mélodine (2012)
The present study investigates the phenomenon of host conformity pressure and its possible consequences on acculturation from immigrants’ perspective. The research is motivated by the discrepancies between results of previous studies on the topic, the relatively small amount of research about immigration in Finland, and the will to examine adaptation issues from an intercultural communication perspective. The study uses different adaptation theories, notably Berry’s (1997) model of acculturative strategies. It also builds on Kim’s (2001) definition of host conformity pressure and Emerson’s (1968) theory of structural power. This research aims at examining (1) what immigrants identify as host conformity pressure, (2) the ways it can affect them, and (3) how they may react to it. Underlying these aims is the intention to identify possible factors for immigrants’ identification of host conformity pressure. Five immigrants living in Finland participated in this qualitative study. In depth theme interviews were conducted, transcribed, and analyzed. Results indicated the existence of host conformity pressure and its absence on both the macro- and micro-levels in 11 different contexts out of which five were related to both phenomena. The participants’ perceptions of host conformity pressure revealed two main types of pressures exerted by the host society: (1) to enforce uniformity and (2) to maintain difference. In addition, the participants’ testimonies showed two main categories of absence of host conformity pressure: (1) bringing immigrants and hosts together and (2) accepting differences. Results revealed that participants’ understanding and stance on the notions of conformity and acculturation were important factors in their perception of host conformity pressure. The study implies that the experience of host conformity pressure can influence immigrants’ acculturation processes especially if it affects their reasons to acculturate. Furthermore, the perceived absence of host conformity pressure can encourage immigrants to develop different acculturation strategies concerning their relationships with hosts and the extent to which they acculturate. This study also suggests that the similarities and differences between immigrants’ and host societies’ characteristics can affect one’s perception of host conformity pressure.